Therapeutic ultrasound alters the physicochemical properties of nanostructured lipid carriers - Jefferson Potiguara de Moraes; Luis Ulisses Signori; Gustavo Orione Puntel; Bianca Vedoin Copês Rambo; Thiago Durand Mussoi; Camila Franco; Virgínia Cielo Rech (O Mundo da Saúde, 2025)
Quercetin has therapeutic potential in the recovery of musculoskeletal injuries; however, when administered orally, this polyphenol exhibits low absorption. Its skin penetration can be enhanced by nanostructured lipid carriers loaded with quercetin (NLC-Q) applied in combination with pulsed therapeutic ultrasound (PTU). However, different intensities of 1 MHz ultrasound may compromise the physicochemical properties of NLC-Q, and this interaction has not yet been evaluated. The aim of this study was to assess the effects of different 1 MHz PTU intensities on the physicochemical properties of a gel containing nanostructured lipid carriers loaded with quercetin (NLC-Q). NLC-Q was developed using the high shear rate method. PTU (1 MHz, for 5 min, 20% duty cycle) was applied to the gel at intensities of 0.1, 0.2, 0.4, and 0.6 W/cm2 SATA (spatial average temporal average intensity). Physicochemical properties (pH, temperature, mean particle size, polydispersity index, and concentrations of quercetin within the nanostructured lipid carriers) were evaluated before and after the application of different PTU intensities. Intensities of 0.1 and 0.2 W/cm2 SATA did not alter the physicochemical properties of NLC-Q, while intensities of 0.4 and 0.6 W/cm2 SATA increased particle size by 14% and 44%, respectively (P < 0.001). These intensities also increased the polydispersity index by 28% and 88% (P < 0.001). PTU intensities above 0.4 W/cm2 SATA lead to instability of NLC-Q within the gel, which does not favor the topical delivery of the active ingredient.